FENOMENA KOMUNIKASI KOMUNITAS K-POPERS PEKANBARU - Putri, Gradini Iradati; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Community of Kpopers become a separate phenomenon for youngster in the middle of society, because of have an uniqueness of life style make this community exist and recognized in Pekanbaru. Some ways do community to communicate the existence of self through by imitating the way they dress and cover boygrup dance moves and his idol girl group. This puprpose of this research was determining the motive members to join the community of Kpopers in Pekanbaru, meaning Korean Pop (K-Pop) for community members Kpopers Pekanbaru and communication experience Kpopers community members in Pekanbaru.This research used qualitative methode by phenomenological approach. The informan of research is 5 who represent community member of Kpopers Pekanbaru who selected by purposive technique.Data collection techniques such as participant observation, in-depth interview, and documentation. This research used data’s analysis technique of phenomenological research according to Creswell by using the technique of persistence observation and extension of participation.The result of research showed that two kindsmotives of community member to join into the community Kpopers Pekanbaru such as because motives form of a hobby dancing that already exist within the community members and the invitation of friends to join the community itself and in order to motives form ofa medium to be known by many people and is also a means to learn about the language and promote themselves and also so that people do not underestimated them. The Korean Pop(Kpop) meaning for Kpopers Pekanbaru community members such as kpop as a medium of selfexpression that is positive and also become a medium for healthy physical community members. Communication experience that community members Kpopers Pekanbaru pleasant communication experience (positive) in the form of acceptance and support from family, add friendship, relations, and get popularity. Second, Negative experience perceived community members Kpopers Pekanbaru such as an underestimated by people and often called “lebay” and also for guys often considered effeminate.Keyword: Phenomenon, Communication, Community, K-popers, Trend Culture